2017
DOI: 10.1371/journal.pone.0186608
|View full text |Cite
|
Sign up to set email alerts
|

Using egocentric analysis to investigate professional networks and productivity of graduate students and faculty in life sciences in Japan, Singapore, and Taiwan

Abstract: Prior studies showed that scientists’ professional networks contribute to research productivity, but little work has examined what factors predict the formation of professional networks. This study sought to 1) examine what factors predict the formation of international ties between faculty and graduate students and 2) identify how these international ties would affect publication productivity in three East Asian countries. Face-to-face surveys and in-depth semi-structured interviews were conducted with a samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The third issue relates to synchronous online interactions. When dealing with global collaboration, the problem of time zones frequently arises [40]. This is certainly an unavoidable issue, and hosts and participants need to compromise.…”
Section: Resultsmentioning
confidence: 99%
“…The third issue relates to synchronous online interactions. When dealing with global collaboration, the problem of time zones frequently arises [40]. This is certainly an unavoidable issue, and hosts and participants need to compromise.…”
Section: Resultsmentioning
confidence: 99%
“…There is also evidence of better research performance among researchers who have more co-authors, and particularly one frequent, primary co-author ( Abbasi et al., 2012 ). Studies have also shown that international collaboration as assessed by connection of a researcher (node) with a collaborator from an institution in a different country is associated with greater academic productivity (number of papers published), particularly among early-career researchers ( Hara et al., 2017 ). Assessing mentorship potential, especially among early-career researchers using network characteristics, is a relatively new field ( National Academies of Sciences, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…An information exchange network (EN) is a type of SNA that explores how people within a network share a specific type of information. 12 SNA has been used to examine ENs among healthcare providers, 13 research faculty, 14 and undergraduate students. 15 In addition, the potential to apply SNA in medical education has recently been described.…”
Section: Introductionmentioning
confidence: 99%